Managing Stakeholder Relationships in CRM Implementation - Foong, Marc (2006)
This report shall focus on the importance of managing stakeholder relationships in CRM implementation at ExxonMobil Lubricants and Specialties. The main motivation behind this research is to study stakeholders'views, perceptions and feelings in the process of CRM implementation. I am also interested to see if ExxonMobil Lubricants and Specialties' CRM implementation met the expectations of stakeholders. Through this research, I hope to share valuable lessons learnt with readers who may be planning IT or CRM project implementation in their organizations.